A novel CoFe2O4@Cr-MIL-101/Y zeolite ternary nanocomposite as a magnetically separable sonocatalyst for efficient sonodegradation of organic dye contaminants from water. Issue 17 (9th March 2020) - Sadeghi, Meysam; Farhadi, Saeed; Zabardasti, Abedin
Abstract : A novel magnetically separable CoFe2 O4 @Cr-MIL-101/Y zeolite ternary nanocomposite was prepared and applied as a sonocatalyst for efficient degradation of organic contaminants. Abstract : In this research, a novel magnetic sonocatalyst nanocomposite, CoFe2 O4 @Cr-MIL-101/Y zeolite, has been successfully fabricated employing a simple hydrothermal method. The as-prepared catalyst was thoroughly identified using Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), energy dispersive X-ray spectroscopy (EDS), EDS elemental dot-mapping, transmission electron microscopy (TEM), atomic force microscopy (AFM), vibrating sample magnetometer (VSM), and nitrogen Brunauer–Emmett–Teller (N2 -BET) analyses. The procured CoFe2 O4 @Cr-MIL-101/Y nanocomposite was then assessed for the decomposition of three types of organic dyes namely methylene blue (MB), rhodamine B (RhB) and methyl orange (MO) from water solution using ultrasound irradiation and subsequently monitored via UV-Vis absorption technique. The sonodecomposition reactions of organic dyes were accomplished in the presence of the H2 O2 solution as a green oxidizing agent. Furthermore, the influence of various experimental independent factors such as irradiation time, process type, initial dye concentration, catalyst dosage, H2 O2 concentration, scavenger type, and catalyst regeneration on the decomposition of MB, RhB and MO were surveyed. Additionally, a first order kinetic model was applied to investigate the sonodecomposition reactions of dye contaminants. The rate constant ( k ) and half-life ( t 1/2 ) data were gained as 0.0675 min −1 and 10.2666 min, respectively, for the decomposition of MB in the US/H2 O2 /CoFe2 O4 @Cr-MIL-101/Y system. Besides, evaluating the attained results, the distinctive performance of ˙OH as the radical scavenger originating from H2 O2 throughout the sonodecomposition process is vividly approved.